Imidazolium cation transportation in a 1-D coordination polymer - Wenqian Chen (2018)
© 2017 The Royal Society of Chemistry. We synthesized a coordination polymer, [EtMeIm][Cu(bpy)(Me 2 PO 4 ) 3 ], containing an anionic 1-D chain and an ethyl methyl imidazolium cation. The organic cations show fast transport behavior, and the observed ion conductivity is 1.4 × 10 -3 S cm -1 at 110 °C. The stability and structure of the material were confirmed by DSC, X-ray adsorption, and long-term AC impedance spectroscopy.